The Louvre (Monterey Home Video, 1978)
This documentary, hosted by Charles Boyer, is a tour of one of the world's great museums. Paris' Louvre. Great works of art such as the Mona Lisa, Winged Victory and Venus De Milo are seen along with a history of the Louvre itself.